Inhibitory Effect of Heparin Inhibitor on Camel Urine Lactoferrin - Ahmad, K. A.; Jada, M. S.; Wurochekke, A. U. (African Multidisciplinary Journal of Sciences and Artificial Intelligence, 2025)
Lactoferrin, an iron-binding protein of the transferrin family, is a basic protein known for its interaction with acidic biomolecules, including heparin proteoglycans. These interactions can influence lactoferrin’s biological functions. This study investigates the inhibitory effect of heparin on lactoferrin activity, revealing a dose-dependent inhibition correlating with increased heparin concentration. Kinetic analysis yielded a Vₘₐₓ of 7.01 U/min, Kₘ of 1037.66 µM, and Kₐₜ of 8.73 × 10⁻¹⁸ s⁻¹, reflecting the enzyme’s catalytic efficiency. Inhibition studies showed that heparin acts as a non-competitive inhibitor, with an IC₅₀, Kᵢ, and K???? all equal to 102.06 µM, indicating moderate affinity for lactoferrin. A binding constant (Kᵦ) of 0.0098 µM⁻¹ further supports this moderate binding interaction. These findings suggest that heparin binds to the N-terminal region of lactoferrin, modulating its function through non-competitive inhibition. The study provides insights into the biochemical regulation of lactoferrin and its interaction with glycosaminoglycans, with potential implications for therapeutic applications involving inflammation and host defense mechanisms.